2020
DOI: 10.1177/0846537120968919
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Society of North America (RSNA) Expert Consensus Statement Related to Chest CT Findings in COVID-19 Versus CO-RADS: Comparison of Reporting System Performance Among Chest Radiologists and End-User Preference

Abstract: Purpose: The RSNA expert consensus statement and CO-RADS reporting system assist radiologists in describing lung imaging findings in a standardized manner in patients under investigation for COVID-19 pneumonia and provide clarity in communication with other healthcare providers. We aim to compare diagnostic performance and inter-/intra-observer among chest radiologists in the interpretation of RSNA and CO-RADS reporting systems and assess clinician preference. Methods: Chest CT scans of 279 patients with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Given that chest CT findings of COVID-19 are not pathognomonic in children, it is use in this population has been questioned. The American College of Radiology currently recommends against using CT as a first line screening test to diagnose COVID-19 and states that chest CT should be reserved for symptomatic hospitalized adults and children with specific clinical indications (117). The International Expert Consensus Statement on Chest Imaging in Pediatric COVID-19 Patient Management does not recommend using CT as the initial diagnostic test in children with suspected disease (115).…”
Section: Laboratory and Imaging Features Of Pediatric Covid-19mentioning
confidence: 99%
“…Given that chest CT findings of COVID-19 are not pathognomonic in children, it is use in this population has been questioned. The American College of Radiology currently recommends against using CT as a first line screening test to diagnose COVID-19 and states that chest CT should be reserved for symptomatic hospitalized adults and children with specific clinical indications (117). The International Expert Consensus Statement on Chest Imaging in Pediatric COVID-19 Patient Management does not recommend using CT as the initial diagnostic test in children with suspected disease (115).…”
Section: Laboratory and Imaging Features Of Pediatric Covid-19mentioning
confidence: 99%
“…The RSNA classification system for reporting COVID-19 pneumonia classified chest CT findings into four categories (negative, atypical, indeterminate, and typical; Table 2 ). Studies have shown its noteworthy diagnostic performance with specific diagnostic thresholds (indeterminate and typical), as well as moderate-to-substantial inter-reader agreement, mostly adopting the SARS-CoV-2 reverse transcription-polymerase chain reaction (RT-PCR) test as the reference diagnostic standard 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It has been reported that CT cannot be used as a screening test, since the positive predictive value of thoracic CT in the diagnosis of COVID-19 is 92% high while the negative predictive value is 42% 7 and the absence of CT findings in the early phase of the disease should not exclude the possibility of COVID-19 disease. 2,8 Clinical It has been reported that the combination of repetitive RT-PCR test and thoracic CT examination is beneficial in cases with suspected COVID-19. 9…”
Section: Introductionmentioning
confidence: 99%